The Relationship Between the Quality of Faith and Depression Risk Among Muslims: A Study from the Perspective of Islamic Psychology - Ermawati (Formad English Foundation NTB Jakarta, 2025)
This study is motivated by the limited research on the relationship between the quality of faith and depression risk among Muslims, despite its significant impact on mental health and well-being in religious communities. The study aims to explore how religiosity, reflected in practices such as prayer, Qur’an recitation, dhikr, and reflective engagement with Islamic teachings, influences depressive symptoms and emotional resilience. The research adopts a qualitative literature review design, analyzing secondary sources from books, journals, and credible studies published within the last ten years. The sample includes multiple scholarly works focusing on religiosity, Islamic psychology, and mental health, selected through purposive sampling. Data were collected through systematic literature analysis and thematic synthesis, guided by frameworks from Islamic psychology and contemporary mental health theories. The findings reveal a significant inverse relationship between the quality of faith and depression risk. Higher levels of religiosity were associated with lower depressive symptoms, improved emotional regulation, enhanced self-confidence, and better coping with life stressors. Practices such as reflective recitation of Al-Fatihah and regular dhikr served as spiritual anchors, fostering hope, reducing despair, and maintaining neurochemical balance, including the regulation of endorphins and neurotransmitters. These results align with both the transactional stress and coping theory and psychoreligious models, supporting the protective role of faith in mental health. The study concludes that faith-based practices play a critical role in enhancing psychological well-being among Muslims. The implications include advancing theoretical understanding of Islamic psychology in mental health and providing practical guidance for mental health practitioners, educators, and religious leaders to integrate spiritual interventions into preventive and therapeutic programs. Future research could empirically examine individual differences, demographic factors, and the effectiveness of faith-based interventions in diverse Muslim populations.